Analisa Cacat Pemotongan Plat Baja SM 490B dengan Menggunakan Gas Cutting Machine CG1-30 di PT. Barat Indonesia (Persero) Divisi Sumber Daya Air - Rendi Setyo Meidianto,; Hadi Wibowo, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze cutting defects in the CG1-30 gas cutting machine on SM 490B material used in the sluice gate manufacturing process at PT. Barata Indonesia (Persero) Air Resources Division. The CG1-30 gas cutting machine is a steel plate cutting machine that plays a crucial role in the sluice gate structure manufacturing process. The methods applied included direct observation, data collection on cutting defects, and documentation of the work process. The analysis revealed several factors that caused defects during the SM 490B steel plate cutting process, including improper nozzle spacing, damage to the drive wheels and rail bearings, and inappropriate cutting speed settings. This analysis aims to reduce fine grain losses and affect the quality of the final product.